Reconfigurable systems for multifunctional electronics. (December 2017) - Zhu, Jia; Dexheimer, Michael; Cheng, Huanyu
Abstract Reconfigurable systems complement the existing efforts of miniaturizing integrated circuits to provide a new direction for the development of future electronics. Such systems can integrate low dimensional materials and metamaterials to enable functional transformation from the deformation to changes in multiple physical properties, including mechanical, electric, optical, and thermal. Capable of overcoming the mismatch in geometries and forms between rigid electronics and soft tissues, bio-integrated electronics enabled by reconfigurable systems can provide continuous monitoring of physiological signals. The new opportunities also extend beyond to human-computer interfaces, diagnostic/therapeutic platforms, and soft robotics. In the development of these systems, biomimicry has been a long lasting inspiration for the novel yet simple designs and technological innovations. As interdisciplinary research becomes evident in such development, collaboration across scientists and physicians from diverse backgrounds would be highly encouraged to tackle grand challenges in this field.